Crab shell polypeptides enhance calcium dynamics and osteogenic activity in osteoporosis - Xiaolei Dong; Xiaolei Dong; Guangmin Zhang; Chong Sun; Hui Zhang; Jinmeng Zhen; Xinlei Li; Xiaohui Xu; Jiane Liu; Xiangzhong Zhao; Yiming Zhang; Linlin Liu; et al. (Frontiers in Pharmacology)
BackgroundOsteoporosis (OP) is a chronic, systemic skeletal disorder characterized by progressive bone loss and microarchitectural deterioration, which increases fracture susceptibility and presents a challenging set of global healthcare problems. Current pharmacological interventions are limited by adverse effects, high costs, and insufficient long-term efficacy. Here, we identify snow crab shell-derived polypeptides (SCSP) as a potent osteoprotective agent.MethodsSCSP were extracted and characterized. Using an ovariectomized (OVX) mouse osteoporosis model, mice received daily oral SCSP (50, 100 mg/kg) or saline for 8 weeks. Bone microstructure (micro-CT), histomorphometry (H&E, Masson, TRAP), immunohistochemistry, and serum bone turnover markers were analyzed. In vitro, SCSP (100, 200 μg/ml) effects on osteogenic/adipogenic differentiation in MSCs/preosteoblasts were assessed via staining (ARS, ALP, Oil Red O) and molecular analyses (Western blot, qPCR, RNA-Seq).ResultsSCSP, enriched in glutamic acid, aspartic acid, and lysine, significantly enhances bone mineral density, restores trabecular architecture, and preserves bone tissue integrity in an ovariectomy-induced OP mouse model without detectable systemic toxicity. At the molecular level, SCSP treatment induces the expression cell cycle regulators and motor protein pathways in osteoblasts while suppressing pro-inflammatory signaling networks, thereby re-establishing osteoblast-osteoclast balance and restoring calcium and phosphorus homeostasis. This combined mechanism promotes osteogenesis while simultaneously suppressing adipogenesis.ConclusionOur findings position SCSP as a promising natural therapeutic for OP and provide key mechanistic insights that may guide future bone-targeted interventions.